Working out of mathematical model of sensitive ferrimagnetic element of the converter - Ларин, В. Ю. (Eastern-European Journal of Enterprise Technologies, 2009)
On the basis of experimental data processing by means of regression analysis methods are received the coefficients for approximating function of the characteristic ferrimagnetic converter, dependence of output voltage circuit on value of equivalent circuit is defined